A bead-spring model for running and tumbling of flagellated swimmers: detailed predictions compared to experimental data for E. coli1. Issue 8 (28th February 2015) - Kong, Miqiu; Wu, Yan; Li, Guangxian; Larson, Ronald G.
<x xml:space="preserve">Abstract</x> To study the swimming of E. coli, we deploy a bead-spring hydrodynamic model (Watari and Larson 2010), whose body and flagellar geometry, motor torques, and motor reversals are adjusted to match the experimental observations of the Berg group (Turner et al. 2000; Darnton et al. 2007) during both running and tumbling of the bacterium.